Issuing and Responding to Unusual Questions: A Conversation Analytic Account of Tom Andersen's Therapeutic Practice. (8th March 2018) - Smoliak, Olga; Le Couteur, Amanda; Quinn‐Nilas, Christopher
Abstract : Tom Andersen is considered one of the key contributors to the development of postmodern practice. Little is known, however, about the ways in which his ideas and practices are routinely carried out in situ . We used Conversation Analysis (CA) to investigate a session of couple therapy facilitated by Andersen. We show how Andersen and client participants oriented to and addressed problems of understanding that occurred between them. The source of this trouble was Andersen's use of unusual question formulations. We offer preliminary evidence that such unusual formulations served particular interactional and institutional (i.e., therapeutic) functions in their local contexts of use. We conclude by considering some implications of this analysis—and of conversation analytic inquiry more generally—for the practice of family therapy.